QLCA and Entangled States as Single-Neuron Activity Generators - Roth, Yehuda (Frontiers in Computational Neuroscience, 2021)
Each neuron in the central nervous system is attached to many dendrites, which provide input information through impulses. Assuming that a neuron’s decision to continue or stop firing is made by rules that are applied to the dendrites’ inputs, we associate the neuron activity with a quantum cellular automaton (QCA) concepts. Following a previous paper that relates the QCA description with entangled states, we provide a quantum description of neuron activity. After reviewing the concept of entanglement expressed by QCA terminology, we propose a model that relates a quantum measurement to consciousness. We then present a toy model that reviews the QCA theory with some adaptation to our terminology. The other parts focus on implementing QCA formalism to describe a single neuron activity.